DEVELOPMENT OF A 5.8 GHz MICROSTRIP TEXTILE ANTENNA BASED ON CORDURA D1682 LAYER SUBSTRATE - Fajar Dwi Artikah; Efri Sandi; Vina Oktaviani (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2024)
This study aims to develop a textile microstrip antenna at a frequency of 5.8 GHz with a layered Cordura D1682 fabric substrate designed to improve the bandwidth performance and characteristics of the antenna. The antenna design is carried out by adding slots to a rectangular patch and optimizing the supply using the inset feed method. This study uses a Research and Development (R&D) approach with simulation and fabrication stages. The antenna substrate made of Cordura with a thickness of 0.55 mm is stacked into three layers so that it has a dielectric constant of 1.9. The results of on-body simulation conditions show a bandwidth of 377 MHz with a VSWR of 1.307, a gain of 7.15 dB, and a SAR value of 0.022 W/kg when attached to the arm, with a unidirectional radiation pattern. Meanwhile, the results of on-body measurements after fabrication produce a bandwidth of 154 MHz with a VSWR of 1.397. These findings indicate that the addition of slots and inset feeds to microstrip textile antennas can improve antenna performance and have the potential to be applied to wearable-based wireless communication systems.